Dampak Perselisihan dan Perceraian Orang Tua Terhadap Kehidupan Religius dan Spiritual Anak - Ahmad Junaidi; Abdul Aziz Wahab; Muhammad Hifdil Islam (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
The purpose of marriage is sakinah, mawadah and warahmah. But, achieving these three things is not easy. The existence of disputes that occur repeatedly is the main factor in the breakdown of a marriage. This dispute can occur due to a lack of trust and communication between partners, so the final path chosen is divorce. The impact of this divorce is not only felt by husband and wife or parents but also by children. Therefore, the purpose of this study is to describe the impact of parental discord and divorce on the religious and spiritual lives of children. This research was conducted at MTs Miftahul Jannah, Wangkal Probolinggo with using a qualitative approach and purposive sampling technique. Data collection techniques included observation, interviews, and documentation of 5 research subjects who met the research criteria. The result obtained is that disputes and divorce have an impact on the child's religious and spiritual life. From a religious perspective, children's obedience to religion, in this case, depends on parenting before and after divorce, while from a spiritual perspective, children tend to mature faster than their age. They are more independent and feel able to find their own solutions to life's problems.